(untitled) (Bioresearch Communications, 2025)
Vegetables play a crucial role in the human diet, providing a rich source of essential nutrients, including vitamins, minerals, fiber, and antioxidants. Regular consumption of vegetables is linked to numerous health benefits and can help prevent various diseases. However, vegetables cultivated in contaminated soil, irrigated with polluted water, and treated with excessive inorganic fertilizers may accumulate harmful heavy metals, posing significant health risks to consumers. This study aimed to evaluate the presence and concentrations of heavy metals in vegetables harvested from areas near industrial zones. Additionally, it assessed the potential health risks associated with the consumption of these contaminated vegetables. The study analyzed four types of vegetables—red spinach, water spinach, cauliflower, and brinjal—for the probable presence of toxic heavy metals, including lead (Pb), cadmium (Cd), nickel (Ni), and chromium (Cr). The concentrations of these metals were measured using an Atomic Absorption Spectrophotometer, with all results expressed on a fresh weight (fw) basis. The health risks associated with the intake of these metals were evaluated through Estimated Daily Intake (EDI) calculations, non-carcinogenic risk assessments using the Target Hazard Quotient (THQ), Total Target Hazard Quotient (TTHQ), and Hazard Index (HI), as well as carcinogenic risk evaluations based on total Carcinogenic Risk (CR). The analysis revealed that the concentrations of heavy metals exceeded the maximum allowable limits set by the FAO/WHO for lead in all vegetable samples, except for water spinach, and for cadmium (Cd) in leafy vegetables. The EDI values for all heavy metals in the vegetables were found to surpass the maximum permissible daily intake (MTDI). While the THQs for all heavy metals, except for lead (Pb) in cauliflower, were below 1, indicating no immediate health hazards for the adult population. The total TTHQs for lead (Pb) and cadmium (Cd) exceeded 1 across all vegetable types, signifying substantial health risks. Bioresearch Commu. 11(2): 1861-1868, 2025 (July)